PENGUKURAN KOEFISIEN DIFFUSE ATENUASI (Kd) DI PERAIRAN DANGKAL SEKITAR KARANG LEBAR, KEPULAUAN SERIBU, DKI JAKARTA - Budhi Agung Prasetyo; Vincentius Paulus Siregar; Syamsul Bahri Agus; Wikanti Asriningrum (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Diffuse attenuation coefficient from downwelling irradiance measurement is one of the important oceanography parameter that provide information on light availability and the light penetration through waters column that represent the waters clarity, photosynthesis and other biological processes. Information about diffuse attenuation coefficient play an important role on the development of bio-optical algorithm on Ocean Color satellite data. The aim of this research is to know the variability of diffuse attenuation coefficient in the shallow water of Karang Lebar, Air and Panggang island using irradiance sensor from hyperspectral radiometer TriOS-RAMSES covering a wavelength range from 320 to 950 nm with 3.3 nm spectral resolution. In situ measurments performed by pull down the irradiance sensor on each depth vertically in waters column up to just before the sea floor. Overall, the measurement result showed that values of Kd(Î») had patterns tends to be decreased on blue-green region wavelength (380-480 nm) and increased again on green-red region (560-760 nm). We found that values of Kd(Î») inside of gobah area had greater values than the outside gobah, significantly the difference significantly occured on all regions that Kd(Î») values measured (F = 5.581 > F critical = 5.554), where each regions has different characteristics to each others. Kd(Î») values dominantly affected by absorbtion of chlorophyll-a with determination cofficient R2 = 0.808 compared with backscattering by suspended solid with determination coefficient R2 = 0.043. Kd(Î») values on visible wavelength regions (400-700 nm) can describe information about how far light can be detected by Ocean Color satellite from water column represented by one optical depth. Relationship of Kd(Î») values with one optical depth can be describe as exponential equation Kd(400-700 nm) = 0.6747*exp(-0.231*1Î¶) with the determination coefficient R2 = 0.97.